Books and Collections Reviews. Issue 1 (1st June 2019) - Goy-Blanquet, Dominique; Hann, Rachel; Lennox, Patricia
Centre National du Costume de Scène: Catalogues to dream byCostumes des Mille et une Nuits, Martine Kahane (ed.) (2008)Saint-Pourçain-sur-Sioule: Bleu autour, 158 pp., p/bkVestiaires de divas, Delphine Pinasa (ed.) (2010)Montreuil: Gourcuff Gradenigo, 191 pp., p/bkLa Source, Ballet de l'Opéra de Paris, Delphine Pinasa (ed.) (2012)Arles: Actes Sud, 191 pp., p/bkShakespeare, l'étoffe du monde, Catherine Treilhou-Balaudé (ed.) (2014)Montreuil: Gourcuff Gradenigo, 158 pp., p/bkModes! A la ville, à la scène, Delphine Pinasa (ed.) (2017)Paris: Somogy éditions d'art, 159 pp., p/bkArtisans de la scène: La fabrique du costume, Delphine Pinasa (ed.) (2017)Paris: Somogy éditions d'art, 159 pp., p/bkThe Tribes: A Walking Exhibition, Sofia Pantouvaki and Sodja Lotker (eds) (2015)Prague: Arts and Theatre Institute, 120 pp., ISBN 978-8-07008-384-0, p/bk, $8.00Fashioning Horror: Dressing to Kill on Screen and in Literature, Julia Petrov and Gudrun D. Whitehead (eds) (2018)London and New York: Bloomsbury Academic, 234 pp., ISBN 978-1-35003-618-5, h/bk, $104